1984
DOI: 10.1085/jgp.84.3.379
|View full text |Cite
|
Sign up to set email alerts
|

Volume-responsive sodium and proton movements in dog red blood cells.

Abstract: Shrinkage of dog red blood cells (RBC) activates a Na transport pathway that is CI dependent, amiloride sensitive, and capable of conducting Na-proton counterflow. It is possible to establish transmembrane gradients for either Na or protons and to demonstrate that each cation species can drive reciprocal movements of the other. The nature of the coupling between Na and proton movements was investigated using the fluorescent probe diS-C3(5) and also by an indirect method in which K movements through valinomycin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
36
0

Year Published

1986
1986
1997
1997

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(40 citation statements)
references
References 23 publications
(71 reference statements)
4
36
0
Order By: Relevance
“…In spite of the fact that NaCl uptake is practically independent of the presence of HCO3-in the external medium and swelling is largely inhibited when Cl-is replaced by N03-, it was suggested that the catecholamine-induced volume increase is mediated by the activation of a Na+-H+ antiport which operates in parallel to a Cl--OH-exchanger, rather than by a NaCl co-transport (Borgese, Garcia-Romeu & Motais, 1986). It should be noted that other systems such as Amphiuma and dog erythrocytes and human blood lymphocytes regulate their volume in response to osmotic shrinkage by the stimulation of a Na+-H+ antiport operating in parallel to a Cl--HC13-exchanger (Cala, 1980(Cala, , 1983bParker, 1983b;Parker & Castranova, 1984;Grinstein, Clarke & Rothstein, 1983;Kregenow, Caryk & Siebens, 1985). These responses do not involve cyclic AMP, however.…”
mentioning
confidence: 99%
“…In spite of the fact that NaCl uptake is practically independent of the presence of HCO3-in the external medium and swelling is largely inhibited when Cl-is replaced by N03-, it was suggested that the catecholamine-induced volume increase is mediated by the activation of a Na+-H+ antiport which operates in parallel to a Cl--OH-exchanger, rather than by a NaCl co-transport (Borgese, Garcia-Romeu & Motais, 1986). It should be noted that other systems such as Amphiuma and dog erythrocytes and human blood lymphocytes regulate their volume in response to osmotic shrinkage by the stimulation of a Na+-H+ antiport operating in parallel to a Cl--HC13-exchanger (Cala, 1980(Cala, , 1983bParker, 1983b;Parker & Castranova, 1984;Grinstein, Clarke & Rothstein, 1983;Kregenow, Caryk & Siebens, 1985). These responses do not involve cyclic AMP, however.…”
mentioning
confidence: 99%
“…In epithelial (Spring and Ericson, 1982) and blood cells (Cala, 1983;Parker and Castranova, 1984;Grinstein et al, 1985b), as well as in Ehrlich ascites cells (Hoffmann, 1985), a regulatory volume increase is observed in response to anisotonic shrinking. Swelling in these cases is thought to be osmotic, due to uptake of solutes and associated water.…”
mentioning
confidence: 99%
“…the intracellular pH would be expected to have decreased to below 7.0 in the previous study [10]. The 'set point' of the Na+/H+ exchanger in Ehrlich cells is 7.0 [31] and the Na+ uptake seen at pH0 7.0 might, therefore, be attributed mainly to an activation of Na+/H+ exchange, which in some systems is anion-sensitive [33], rather than Na+-dependent anion exchange. This is also supported by the observation that net Na+ influx was lower at pH0 7.0 than at 7.4, in agreement with the observation that pH re covery by Na+/H + exchange is slower and less complete than by Na+-dependent anion ex change [23].…”
Section: Discussionmentioning
confidence: 74%